2000
DOI: 10.1046/j.1523-1747.2000.00915.x
|View full text |Cite
|
Sign up to set email alerts
|

Signaling of Mechanical Stretch in Human Keratinocytes via MAP Kinases

Abstract: Cells within human skin are permanently exposed to mechanical stretching. Here we present evidence that alterations in cell shape trigger biochemical signaling via MAP kinases in human keratinocytes. In an in vitro attempt we demonstrate a fast but transient activation of extracellular signal-regulated kinases 1/2 in response to cell stretch. This activation is reversed by preincubation with functional blocking antibodies directed towards beta1-integrins. As a second member of MAP kinases, stress-activated pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
118
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(126 citation statements)
references
References 32 publications
8
118
0
Order By: Relevance
“…The molecular mechanisms that regulate KRT9 expression remain largely unknown, although pressure and mitogen-activated protein kinase signaling contribute. 12,13 Until now, it was assumed that KRT9 expression was mostly under the control of site-specific volar fibroblasts. Indeed, despite a mixed primary literature, 33e37 it has been commonly hypothesized that primary signals from fibroblasts exclusively dictate epidermal skin identity through epithelial-mesenchymal interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular mechanisms that regulate KRT9 expression remain largely unknown, although pressure and mitogen-activated protein kinase signaling contribute. 12,13 Until now, it was assumed that KRT9 expression was mostly under the control of site-specific volar fibroblasts. Indeed, despite a mixed primary literature, 33e37 it has been commonly hypothesized that primary signals from fibroblasts exclusively dictate epidermal skin identity through epithelial-mesenchymal interactions.…”
Section: Discussionmentioning
confidence: 99%
“…KRT9 can be activated by pressure-activating mitogen-activated protein kinases. 12,13 To further study the mechanism of KRT9 regulation, Moll et al 14 reported that volar fibroblasts induce ectopic nonvolar KRT9 expression in keratinocytes, as rarely is the case in vivo. Grafting of human volar fibroblasts together with nonvolar keratinocytes generated thickened KRT9 þ human epidermis on severe combined immunodeficiency mice.…”
mentioning
confidence: 99%
“…Microarray analysis performed on mechanical stretched and normal human skin revealed an up-regulation of AP-1 in mechanically stretched skin (Yang et al 2011). Other stimuli of AP-1 include growth factor signaling via mitogen-activated protein (MAP) kinases, which are also activated in response to mechanical stress (Kippenberger et al 2000). AP-1 acts as a homodimeric or heterodimeric transcription factor composed of members of the Fos (c-Fos, FosB, Fra-1, and Fra-2) and Jun (c-Jun, JunB, and JunD) families.…”
Section: Mechanosensitive Signaling Pathways In the Control Of Desmosmentioning
confidence: 99%
“…Exposure of keratinocytes to stretch results in rapid and transient induction of MAPK ERK1/2 and SAP kinases (Kippenberger et al 2000;Yano et al 2004), accompanied by altered keratin expression, increased keratin phosphorylation and reorganization of keratin networks (Yano et al 2004;Snider and Omary 2014). At least in keratinocytes, mechanical stretching acts via induction of calcium influx, EGFR phosphorylation, and ERK1/2 activation (Yano et al 2004).…”
Section: Impact Of Mechanical Stretch On the Desmosome -Keratin Complexmentioning
confidence: 99%
“…The classical ligand for integrins on fibroblasts is fibronectin, which contains the integrin-recognition sequence RGD (31). Specific integrin blocking antibodies or RGD peptides have been widely used to verify involvement of integrins in mechanotransduction (32)(33)(34)(35). To determine whether integrins could mediate the signaling events in response to acoustic pulsed energy, skin fibroblasts were treated with an integrin ␤ 1 blocking antibody…”
Section: Fig 1 Us Induces Increase In Cell Proliferation Of Human Smentioning
confidence: 99%